Drying Onion Slices using a Food Dehydrator - Arianto Passalli Sarjono; Suherman Suherman (Eduvest - Journal of Universal Studies, 2022)
Shallots are one of the mainstay products of Demak Regency which are continuously being developed. However, the Demak Shallot Cluster faces a major obstacle, namely drying technology, which is the main cause of the decline in competitiveness, and farmers suffer huge losses. Therefore, in this study, a study of the drying of sliced shallots using a food dehydrator will be carried out. The research analysis includes (1) Drying Characteristics, (2) Drying Rate Analysis, (3) Application of Thin Layer Drying Model, (4) Rehydration Ratio Analysis, (5) Color Analysis, (6) Flavonoid and Total Phenolic Analysis, (7) Antioxidant Activity Analysis. The quality parameters of shallot products in general will follow SNI 3159-2013, this standard stipulates provisions regarding the quality, size and hygiene of shallots (Allium cepa varascalonicum) of the Alliaceae family for consumption, plus the strength of onion bulbs, identification and quantification of flavonoid compounds, and anthocyanin levels. The results showed that the moisture ratio value in equilibrium was 9.34% with the fastest drying occurring at a temperature of 60 oC , which was 0.938 g/minute. The three thin layer drying models were analyzed to determine the appropriate thin layer drying model. The Page model was chosen because it has an R value of 2 the highest is 0.9353 and the lowest RMSE and x 2 values are 0.04354 and 0.0025 3. Changes in color and bioactive compounds in the dried onion slices are caused by heat which causes damage to bioactive compounds. Based on the parameters that have been determined, a temperature of 50 o C indicates the optimum temperature for drying shallot slices.